Vanilla pompona Schiede (Vanilloideae-Orchidaceae): Morphological Variation of the Labellum in the Mexican Localities of Veracruz, Puebla, Jalisco and Oaxaca - Cecilia Viveros-Antonio; Adriana Delgado-Alvarado; Angel Bustamante-González; Jesús Hernández-Ruíz; Ma. de Lourdes Arévalo-Galarza; Braulio Edgar Herrera-Cabrera (Diversity, 2023)
Vanilla pompona is the third most important commercial species of the genus Vanilla, but the morphometric variation of its flowers is not well known. In orchids, infraspecific variation is expressed in the labellum. This study had the objective of analyzing the floral variation of V. pompona collections from the localities in Veracruz, Puebla, Jalisco and Oaxaca, in Mexico. During the flowering period, we obtained 55 collections of V. pompona flowers, and the labellum of each flower was dissected. We used ImageJ to measure and portray 54 lines and 7 angles in these labella. With the data obtained, we performed an analysis of variance, principal component analysis and cluster analysis. The results showed significant differences among the collections and localities in the means of the lines of the basal, middle, and apical regions of the labellum. Also, six morphotypes were obtained, and we found that variation was associated with factors such as the environment, geographic barriers, and pollinator pressure. Moreover, we observed variation in flowering periods in one locality of Veracruz. We concluded that there is infraspecific variation within and between the collection localities of V. pompona in the Atlantic region (Puebla and Veracruz) and the Pacific region (Jalisco and Oaxaca), Mexico.